Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi di PT. ASIA HEALTH ENERGI BEVERAGES SUKABUMI) - Buci Morisson Morisson (Program Studi Manajemen, Universitas Al Ghifari, 2020)
Based on multiple regression analysis obtained by linear regression equation Y = 13,531 + 0,321X1 + 0,420X2 + e. Stating that the effect of increasing the value of the leadership unit by 0.321 then the value of employee performance will increase by 32.1%. If work motivation has an additional value of 0.420, the employee's performance value will also increase by 42,0%. Based on the calculation of the coefficient of determination obtained Adjusted (R square) value of 0.446 or 44.6% and the remaining 55.4% is influenced by variables not examined. Based on the calculation of the correlation coefficient, the value is 0.681, the coefficient is at an interval of 0.60 - 0.799, included in the level of